(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The White Paper on e-Education1 promotes the use of various information communication technologies (ICTs) to achieve the expected learning outcomes in the different learning areas of the school curriculum. Because most teachers and learners are not yet computer skilled, resource-based learning, supported by digital versatile disc (DVD) technology, is one of the most cost-effective and self-contained educational media that involve minimal infrastructural investment. Educational DVDs provide the opportunity to deliver a constructive multi-media learning experience to learners in rural areas who do not have access to libraries and the Internet. This is especially valuable for history education because DVDs allow learners to “go time travelling” through history, guided by different learning media and artefacts such as historical photographs, illustrations, film material, music, speeches, newspaper reports, political cartoons, maps, etc. Multi-media learning tools stimulate different learning styles and broaden the range of the learning experience in general. This paper provides a research framework for the development and evaluation of educational DVDs and Web-based multi-media clips for grades 8 and 9 history in the social sciences learning area. These clips are currently being developed at the Faculty Education Sciences of the North-West University. These educational media, with accompanying teacher manual and learner word-cards, are intended as inexpensive support of quality education and sustainable social development in South Africa.